2008
DOI: 10.1037/0882-7974.23.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Reported exposure and emotional reactivity to daily stressors: The roles of adult age and global perceived stress.

Abstract: A central goal of daily stress research is to identify resilience and vulnerability factors associated with exposure and reactivity to daily stressors. The current study examined how age differences and global perceptions of stress relate to exposure and emotional reactivity to daily stressors. Sixty-seven younger (M age = 20) and 116 older (M age = 80) adults completed a daily stress diary and measures of positive and negative affect on 6 days over a 14 day period. Participants also completed a measure of glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
280
3
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 247 publications
(315 citation statements)
references
References 43 publications
(71 reference statements)
28
280
3
4
Order By: Relevance
“…Previous daily stress research has shown that negative mood is higher on stressor days as compared to nonstressor days (e.g., Stawski, Sliwinski, Almeida, & Smyth, 2008). Therefore, we continue our example by examining to what extent the observed associations between daily stress and physical symptom reports would remain after controlling for negative mood.…”
Section: Person-mean-centering Of a Time-varying Predictor Of Daily Nmentioning
confidence: 91%
“…Previous daily stress research has shown that negative mood is higher on stressor days as compared to nonstressor days (e.g., Stawski, Sliwinski, Almeida, & Smyth, 2008). Therefore, we continue our example by examining to what extent the observed associations between daily stress and physical symptom reports would remain after controlling for negative mood.…”
Section: Person-mean-centering Of a Time-varying Predictor Of Daily Nmentioning
confidence: 91%
“…social or ethnic group) and also as a result of genetic factors (Cameron et al, 2007). For example, shared family and unique environmental effects have been reported to account for the variance in perceived severity of daily stressors (Charles & Almeida, 2007) which is in turn a determinant of resilience (Stawski, Sliwinski, Almeida, & Smyth, 2008). In addition, the influence of a unique environment on perceived stress has been observed to exert a stronger influence on older adults irrespective of gender (Charles & Almeida, 2007).…”
Section: Current Conceptualisations Of Resiliencementioning
confidence: 99%
“…However, when affective reactivity to daily stressors is measured directly, some findings challenge propositions of a reduction in older age. Evaluations of stressor severity and affective reactivity to daily stressors were sometimes shown to be lower in older compared with younger adults (Birditt et al, 2005;Stawski, Almeida, Lachman, Tun, & Rosnick, 2010;Uchino, Berg, Smith, Pearce, & Skinner, 2006), but also stronger (Mroczek & Almeida, 2004), or invariant across age groups (e.g., Stawski, Sliwinski, Almeida, & Smyth, 2008). Methodological differences across studies as well as the sampling of stressor types may contribute to a heterogeneous picture of findings (Röcke, Li, & Smith, 2009;Stawski et al, 2008).…”
Section: Adult Age Differencesmentioning
confidence: 99%